Distribution and Clinical Characteristics of Endometriosis in a Tertiary Referral Hospital in Indonesia: A Cross-Sectional Study - Salsabilah Aisyah Putri; Yusuf Effendi; Abarham Martadiansyah; Fatimah Usman; Sonia Prima Arisa Putri (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objective: The objective of this study is to describe the prevalence and distribution of demographic and reproductive characteristics among patients diagnosed with endometriosis at a tertiary referral hospital in Palembang, Indonesia.Methods: This is a descriptive cross-sectional study that was conducted on secondary medical record data of women with histopathologically-confirmed endometriosis between the period of July 2022 to December 2024 to achieve the objective mentioned previously by applying total sampling. Variables analyzed included age, age at menarche, menstrual cycle pattern, disease stage based on the revised American Society for Reproductive Medicine classification, marital status, parity, and body mass index. Data were then summarized using descriptive statistics.Results: A total of 507 patients were included. The highest number of cases occurred in 2024 (57.2%). Most patients were aged between 15 – 49 years (98.4%), had menarche at 8 – 15 years (98.8%), and regular menstrual cycles (98.0%). Stage IV was predominant (61.1%). Nearly half were nulliparous (49.5%), were married (94.1%), and had normal body mass index (38.5%).Conclusion: Most patients with endometriosis in this study were of reproductive age and were predominantly diagnosed at an advanced stage with nulliparity frequently observed.Distribusi dan Karakteristik Klinis Endometriosis di Rumah Sakit Rujukan Tersier di Indonesia: Studi Potong LintangAbstrakTujuan: Penelitian ini bertujuan untuk mendeskripsikan prevalensi dan distribusi karakteristik demografi serta reproduksi pasien endometriosis di rumah sakit rujukan tersier di Palembang, Indonesia.Metode: Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan desain potong lintang menggunakan data sekunder rekam medis pasien endometriosis yang terkonfirmasi secara histopatologi periode Juli 2022 hingga Desember 2024. Variabel yang dianalisis meliputi usia, usia menarche, pola siklus menstruasi, derajat berdasarkan klasifikasi Revised American Society for Reproductive Medicine, status pernikahan, paritas, dan indeks massa tubuh. Data dianalisis menggunakan statistik deskriptif.Hasil: Hasil penelitian menunjukkan bahwa sebanyak 507 pasien memenuhi kriteria. Kasus terbanyak ditemukan pada tahun 2024 (57,2%). Mayoritas pasien berusia 15 – 49 tahun (98,4%), usia menarche 8 – 15 tahun (98,8%), dan siklus menstruasi teratur (98,0%). Stadium IV mendominasi (61,1%). Sebanyak 49,5% pasien merupakan nulipara, 94,1% telah menikah, dan 38,5% memiliki indeks massa tubuh normal.Kesimpulan: Sebagian besar pasien endometriosis dalam penelitian ini merupakan wanita usia reproduktif dan terdiagnosis pada stadium lanjut dengan nuliparitas sebagai karakteristik yang sering ditemukan.